2019
DOI: 10.1073/pnas.1910666116
|View full text |Cite
|
Sign up to set email alerts
|

Population-based neuroimaging reveals traces of childbirth in the maternal brain

Abstract: Maternal brain adaptations have been found across pregnancy and postpartum, but little is known about the long-term effects of parity on the maternal brain. Using neuroimaging and machine learning, we investigated structural brain characteristics in 12,021 middle-aged women from the UK Biobank, demonstrating that parous women showed less evidence of brain aging compared to their nulliparous peers. The relationship between childbirths and a “younger-looking” brain could not be explained by common genetic variat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
68
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 52 publications
14
68
0
Order By: Relevance
“…Though application of brain-aging algorithms in a midlife population is still relatively novel, previous literature using a similar technique to analyze brain-PAD (brainageR, https://github.com/james-cole/brainageR ) has shown that accelerated brain aging may be observable in midlife women in relation to lifestyle factors which impact hormone levels, in this case number of childbirths. Further, their findings are consistent with observed patterns of parity and risk of AD, where increased number of childbirths conveys lower risk of neurocognitive decline (de Lange et al, 2019 ). This provides additional evidence that brain-PAD at midlife could relate to later life outcomes and that female populations experience hormonal changes throughout their life that convey unique risk factors for neurocognitive decline.…”
Section: Discussionsupporting
confidence: 83%
“…Though application of brain-aging algorithms in a midlife population is still relatively novel, previous literature using a similar technique to analyze brain-PAD (brainageR, https://github.com/james-cole/brainageR ) has shown that accelerated brain aging may be observable in midlife women in relation to lifestyle factors which impact hormone levels, in this case number of childbirths. Further, their findings are consistent with observed patterns of parity and risk of AD, where increased number of childbirths conveys lower risk of neurocognitive decline (de Lange et al, 2019 ). This provides additional evidence that brain-PAD at midlife could relate to later life outcomes and that female populations experience hormonal changes throughout their life that convey unique risk factors for neurocognitive decline.…”
Section: Discussionsupporting
confidence: 83%
“…Physical activity was measured using ankle-worn accelerometer across on average 7 days (range 3 to 9) and physical capabilities were operationalized through grip strength, walking speed, and postural control as a measure of balance. Based on recent implementations and the use of an independent training set, we estimated individual brain age using global and subcortical gray matter from T1-weighted MRI (de Lange & Cole, 2020; de Lange et al, 2019; Kaufmann et al, 2019). We used an independent training set comprising MRI data from 2407 healthy individuals for brain age prediction, and applied the cross-validated models in our unseen test set.…”
Section: Introductionmentioning
confidence: 99%
“…The first PC captures the largest amount of variation in the computed PRSs and thus could have better discrimination of the phenotype we are testing. This strategy was recently implemented in studies of polygenic effects on schizophrenia as well as brain imaging (Alnaes et al, 2019;Bergen et al, 2019;De Lange et al, 2019;Maglanoc et al, 2019). This unsupervised approach incorporates all computed scores across a range of tuning parameters and, importantly, is agnostic regarding the outcome of interest and thereby maintains correct Type I error.…”
Section: Introductionmentioning
confidence: 99%